The effects of scolocidal agents on hepatopancreaticobiliary system “An experimenal study” - Burhan EYÜPOĞLU; Mutlu DOĞANAY; Erhan REİS and Yunus Nadi YÜKSEK and Sezer KULAÇOĞLU and Nuri Aydın KAMA (Turkish Journal of Gastroenterology, 2019)
-